(untitled) (Journal of Comparative & International Higher Education, 2024)
This paper examines the digitalization of higher education in Ethiopia. It mainly focuses on better understanding the policies, practices, and challenges of digitalization of higher education in the country. The necessary data were mainly generated from continental, national, and institutional policy and strategy documents. Publicly available transnational and national reports and other documents and the author’s views and lived experiences were also used to substantiate data generated through policy review. The data were analyzed using deductive thematic analysis. The themes were mainly developed based on prior research and existing literature. The findings indicate that there are sufficient and feasible policies and strategies to promote and ensure the digitalization of higher education in Ethiopia. The findings also reveal that there are initiatives that promote the practice of digitalization of higher education. However, poor internet connection, lack of adequate ICT infrastructure, lack of skilled human resources, and staff resistance to change were found to be the major barriers to enhancing the digitalization of higher education in Ethiopian higher education. The results imply that having feasible policies and strategies is a necessary but insufficient condition to ensure effective implementation of digitalization of higher education. It necessitates the government’s commitment as well as a shift in focus from the expansion of HEIs, which was the case in the last two decades, to ensuring the quality and relevance of HEIs through digital transformation.